From Pandemic to Prevention: Insights from COVID-19 Vaccination Attitudes in Individuals with Schizophrenia - Felipe Soto-Pérez; Andrea Lettieri; Carmen Pita González; Sonia Miguel Criado; Manuel A. Franco-Martín (COVID)
Awareness about the attitudes towards the vaccination of persons with schizophrenia is essential, as this group has a greater likelihood of experiencing serious consequences if infected with COVID-19 or other infectious processes. For this reason, 141 persons with schizophrenia completed a survey addressing different aspects of receiving the vaccine for COVID-19. In general, the results are similar to those of people without a severe mental disorder. Persons with schizophrenia were willing to get vaccinated, perceived vaccination as being as safe and effective as the general population did, and reported that they usually followed preventive measures to avoid the spread of the virus. However, their concerns were frequently related to possible health problems or fears about the vaccination. There is no influence from sociodemographic variables, though limited social life, perceived risk in people in their immediate environment, and a negative self-assessment of their own health were associated with increased acceptance of vaccination. Thus, the present study provides useful information on this topic and encourages the development of programs and interventions that promote preventive actions for this group of people.